Strategi Pemasaran untuk Meningkatkan Omzet Penjualan Air Minum Dalam Kemasan pada CV. Satria Putra Jaya di Tabanan - Putri Anggreni (Universitas Negeri Surabaya, 2018)
CV. Satria Putra Jaya is a company plant Drinking Water (bottled water). In conducting its business, the marketing strategy is a process that plays an important role against companies that market goods and services to consumers because every company has an equal chance in producing goods or services, so it can only be competition between companies and competitors in the market to seize, in addition to marketing strategy the role of existing employees also affect the increase in sales volume. Results of the analysis of internal factors is the main force that the company uses its own capital (a score of 0.340). The Company has no burden to return the money to the Bank. While the main weaknesses in internal factors, namely the lack of education and training for employees (score 0.151). Total score of 2,640 IFE matrix shows that the company is currently in a state of being. The result of external factors which are the main opportunities CV. Satria Putra Jaya namely the cooperation join label logo on the packaging for the hotel, restaurant and cafe (score 0.396). While the main threats that arise for the company which is the number of new competitors entering the drinking water industry (score 0.163). Total score of 2,576 EFE matrix shows that the condition of the company is currently in a state of moderate/average. Both results IFE and EFE matrix when inserted into the matrix of IE then conditions the company is currently in a quadrant V, which means the conditions to keep and maintain. Alternative strategies derived from the SWOT matrix, namely, 1) Utilizing a strategic location in order to attract potential customers, 2) Maintaining price and improve product quality, 3) Improve the quality of human resources, 4) Adding a branch and distribution network to increase sales volume, 5) Increases vehicle distribution to increase the coverage and seeking greater market share by penetrating the market